Acoustic And Aerodynamic Installation Effect On Phase-Controlled Small Rotor-Rotor Configurations - Yin, J.; Rossignol, K. S.; Delduchetto, F.; Candeloro, P.; Pagliaroli, T. (My University, 2025)
The effects of acoustic and aerodynamic installations on the noise properties of phase-controlled small rotor-rotor configurations are studied using a common test conducted by Unicusano and DLR and numerical tools developed by DLR. The test data for the phase-controlled rotor used in the study were obtained in the DLR low-speed acoustic wind tunnel (AWB) in Braunschweig, as part of the common test conducted by DLR and Unicusano in the context of the GARTEUR Action Group HC/AG-26. For the simulations, a numerical approach combining a free wake panel method and a Ffowcs Williams-Hawking formulation was used to consider the aerodynamic installation and provide the incident sound field to a boundary element method, in which the acoustic installation effect was simulated. Comparisons indicate that considering only the aerodynamic installation does not match the test results. Acoustic scattering leading to a noticeable amplification of noise levels is clearly demonstrated. The scattered field must be considered when defining appropriate phase offsets between rotor pairs to create destructive interference of sound waves.